2012
DOI: 10.1111/j.1600-0625.2012.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B‐induced LGI3 secretion protects human keratinocytes

Abstract: Leucine-rich glioma inactivated 3 (LGI3) is known to be expressed mainly in the brain. However, the expression and physiological roles of LGI3 in skin cells remain unknown. In this study, it was found for the first time that LGI3 is expressed mostly by normal human keratinocytes. Furthermore, ELISA analysis showed that HaCaT human keratinocytes increased LGI3 secretion after exposure to ultraviolet B (UVB) in a time-and dose-dependent manner. We next investigated the possible role of LGI3 in keratinocytes. LGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…LGI3-promoted neurite outgrowth was mediated by Akt and FAK 3. p53 and MDM2 were shown to be involved in LGI3-promoted cell survival in UVB-irradiated keratinocytes 5. β-Catenin and GSK3β mediated keratinocyte migration induced by LGI3 7.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…LGI3-promoted neurite outgrowth was mediated by Akt and FAK 3. p53 and MDM2 were shown to be involved in LGI3-promoted cell survival in UVB-irradiated keratinocytes 5. β-Catenin and GSK3β mediated keratinocyte migration induced by LGI3 7.…”
Section: Discussionmentioning
confidence: 97%
“…LGI3 is also expressed in skin and adipose tissues 4,5. We showed that LGI3 secretion was induced by ultraviolet B (UVB) and promoted keratinocyte survival 5. We demonstrated that LGI3 promoted the migration of keratinocytes and melanogenesis 6,7…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides the nervous system, LGI3 is expressed in diverse tissues including skin and adipose tissues [4,5]. We reported that ultraviolet B-irradiation-induced secretion of LGI3 promoted survival of human keratinocytes [5]. We also showed that LGI3 promoted keratinocyte migration and melanocyte pigmentation [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…We previously showed that LGI3 played regulatory roles in neuronal exocytosis and differentiation [2,3]. Besides the nervous system, LGI3 is expressed in diverse tissues including skin and adipose tissues [4,5]. We reported that ultraviolet B-irradiation-induced secretion of LGI3 promoted survival of human keratinocytes [5].…”
Section: Introductionmentioning
confidence: 97%